Correlation of the concepts «movable» and «real» estate in the light of the foreign legal systems’ experience - Нікітіна, Зоя Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article discusses the concept of movable and real estate in the Ukrainian and foreign legal systems.Determinative in formation of conflict rules in the property issues is division of property (things) on themovable and immovable particularly in all states. It causes the determination of property rights, the form andterms of the transfer of ownership of this property. The results of this research may be used for further studyof relation of movable and immovable property.